Islam and Economic Development: Exploring the Role of Indonesian Muslim Society in Developing Islamic Microfinance Institution - Ayi Yunus Rusyana (International Journal of Nusantara Islam, 2014)
Although a religion is considered as a one of the cultural barriers that can impede an economic development, nevertheless in this paper I prove that Islam as well as Muslim society has a big role to empower economic life in Indonesian Muslim. The growth of Bayt al-Māl wa al-Tamwīl (BMT), Islamic microfinance institution, initiated by Muslim community is a great evidence on how religioun gave a positive impact in economic development in Indonesia. Using the theory of collective action proposed by Alberto Melucci, I explore the main factors that influenced Muslims to establish BMT, and how BMT movement develops in Indonesian Muslim society. Overall, in this paper I argue that the BMT movement can be considered as a social movement where the civil society takes more important role than the state. Interestingly, the lack of regulation is not becoming an obstacle for Muslim society to establish and develop BMT in some regions in Indonesia.